Reciprocal regulation of calcium-/phosphate-regulating hormones in cyclists during the Giro d'Italia 3-week stage race0 - Lombardi, G.; Corsetti, R.; Lanteri, P.; Grasso, D.; Vianello, E.; Marazzi, M. G.; Graziani, R.; Colombini, A.; Galliera, E.; Corsi Romanelli, M. M.; Banfi, G. (Scandinavian Journal of Medicine & Science in Sports, 2014)
Calcium and phosphate are essential for cell functions, and their serum concentrations result from the balance between intestinal absorption, bony storage, and urinary excretion. Fibroblast growth factor 23 (FGF23), expressed by osteocytes and osteoblasts, acts in the kidney, leading to hypophosphatemia and low 1,25-dihydroxycholecalciferol synthesis, but suppresses parathyroid function. The aim of this study was to explore the effects of a high-energy demanding cycling race on this bone-kidney-parathyroid axis. We studied nine cyclists during the 2011 Giro d'Italia stage race. Pre-analytical and analytical phases followed academic and anti-doping recommendations. Serum parathyroid hormone (PTH), 25(OH)D, total calcium, inorganic phosphorus, and plasma FGF23 were measured on days -1, 12, and 22 and corrected for changes in plasma volume. Dietary calcium and phosphorus, anthropometric parameters (height, weight, and body mass index) and indexes of metabolic effort (net energy expenditure, power output) were recorded. Dietary calcium and phosphorus intakes were kept at the same levels throughout the race. Twenty-five (OH)D, PTH, and calcium concentrations remained stable. FGF23 increased 50% with a positive correlation with the indexes of metabolic effort and, consequently, phosphorous decreased, although only in the first half. The strong metabolic effort acts on the bone-kidney-parathyroid system, and the rise in FGF23 plasma concentration might be aimed at maintaining calcium and phosphorus homeostasis.